DAMPAK KREDIT TERHADAP PENDAPATAN USAHATANI KOPI ARABIKA - Sarah Setiasih Dharmawan; Tuti Karyani (JURNAL AGRIBISNIS TERPADU, 2018)
Margamulya, Pangalengan is one of coffee producing region with the Java Preanger arabica coffee brand marketed by Margamulya Coffee Producers Cooperative. Java Preanger is sold to domestic and abroad, so then coffee production should be available in large quantities. Productions by somefarmers is low becaused does not do maintenance properly. The purpose of this research is to know the impact of credit on arabica coffee income. This research used inferential quantitative methods. The analysis tested by Independent Sample T-Test. Sampling done by Simple Random Sampling methods. The results state that credit provides a significant difference in arabica coffee income for farmers credit recipients and non-credit recipients because their used for arabica coffee farming and for labor wages.